Analisis Kasus Pelanggaran Etik Akuntan Publik pada PT. Sunprima Nusantara Pembiayaan (SNP Finance) - Mei, Cing; Mulyati, Desi; Julianto, Julianto (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2022)
Financial statements contain information that describes the condition of the company and serves as a basis for making decisions for external and internal parties. Therefore, auditors are needed to assess the validation of the information presented is in accordance with applicable standards through opinions in the audit report. Auditors must behave professionally and ethically according to the Public Accountant Code of Ethics. Nowadays, fraud cases are still prone to occur, one of which occurred in SNP Finance, even though the financial statements have been audited. This encourages researchers to explore further the causes and whether auditors has complied with the applicable code of ethics. The research method used is a qualitative approach with descriptive results. The results showed that the auditors involved have violated the principles of integrity, objectivity, competence and prudence, and professional behavior. The fatal mistake was issuing an unqualified opinion which misled report users in making decisions.